Meritocracy or malfeasance: violations of meritocracy erode civic rule following - Kline, Reuben; Galeotti, Fabio; Orsini, Raimondello (Frontiers in Behavioral Economics, 2025)
The perceived legitimacy of institutions, along with the voluntary compliance with authority that it undergirds, is crucial for stable governance and economic development. Legitimacy varies greatly across individuals and societies. We introduce a simple model of meritocratic equity—the notion that in a social exchange, individuals should receive greater compensation if their contributions exceed those of others. We argue that violations of meritocratic equity undermine the legitimacy of authority, leading to breaking rules, laws and civic norms—behaviors we refer to as justified malfeasance—in an effort to reduce perceived inequity. Using data from an incentivized laboratory experiment conducted in the United States and Italy and complemented by data from the World Values Survey, we investigate the effect of meritocratic violations on malfeasance. We find convergent evidence that meritocratic inequity explains variation in justified malfeasance across individuals and across countries. We conclude by discussing the implications of our results for multiple equilibria in societal levels of malfeasance and voluntary compliance with authority.